Gendered Solutions to the Care Gap Issue in Iceland. Issue 4 (1st October 2016) - Ingólfsdóttir, Edda Sigurbjörg; Gíslason, Ingólfur V.
Abstract: Iceland has for some years enjoyed an international reputation as one of the most gender-equal societies in the world. It has also received a fair amount of international attention for an innovative approach to making parental leave compatible with gender equality by dividing the period into three equally long parts with non-transferable periods reserved for both parents. Still, there is a fairly long period that needs bridging from when parental leave ends and public day-care for children begins. During this intervening period parents have to find their own solution for childcare. We interviewed Icelandic parents about their use of parental leave and the bridging of the care gap period and argue that this gap is a major hindrance in the realization of the gender equality goals of the law on parental leave. We also note that unequal division of parental leave is generally not considered to violate the ideal of gender equality.